The soil underfoot infinite possibilities for a finite resource - Churchman, G. J.; Landa, Edward (CRC Press/Taylor and Francis, 2014)
The largest part of the world's food comes from its soils, either directly from plants, or via animals fed on pastures and crops. Thus, it is necessary to maintain, and if possible, improve the quality-and hence good health-of soils, while enabling them to support the growing world population. The Soil Underfoot: Infinite Possibilities for a Finite Resource arms readers with historical wisdom from various populations around the globe, along with current ideas and approaches for the wise management of soils.